2019
DOI: 10.7717/peerj.7440
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Doppler flow systolic blood pressure measurements taken with and without headphones in privately-owned, conscious dogs

Abstract: Objective The purpose of this study was to assess the effect of headphone use and covariates on indirect radial Doppler flow systolic arterial blood pressure (BP) measurements in dogs. Methods Between May and August 2018, 100 privately-owned dogs were enrolled. Blood pressure was measured in lateral recumbency, with and without headphones, using a randomized crossover design. The initial BP, mean of BP 2-6, weight, BCS, MCS, anxiety score, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…A study in client-owned dogs showed that only the first BP measurement was higher when taken without headphones; however, the five subsequent readings and the average of the five readings were not. 26 As previously mentioned, one published abstract with healthy and diseased client-owned cats reported no significant differences in direct Doppler flow BP measurements collected with and without headphones 8 weeks apart. 11 This is the first study that considers age to be a factor.…”
Section: Discussionmentioning
confidence: 83%
“…A study in client-owned dogs showed that only the first BP measurement was higher when taken without headphones; however, the five subsequent readings and the average of the five readings were not. 26 As previously mentioned, one published abstract with healthy and diseased client-owned cats reported no significant differences in direct Doppler flow BP measurements collected with and without headphones 8 weeks apart. 11 This is the first study that considers age to be a factor.…”
Section: Discussionmentioning
confidence: 83%
“…O uso de fones de ouvido pode ser uma alternativa para pacientes que apresentam sinais de incômodos com ruídos. Gill et al (88) conduziram um estudo com objetivo de analisar o impacto do uso de fones de ouvido e variáveis associadas na obtenção dos valores pressóricos pelo método indireto em cães. Os autores observaram que não houve diferenças entre o uso ou não dos fones de ouvido para cães, embora os valores de pressão da primeira rodada estivessem mais altos no grupo sem.…”
Section: Diagnósticounclassified
“…Além disso, o uso dos fones possibilitou uma melhor acurácia dos resultados. A aferição pressórica deve ser realizada de forma adequada, de forma que, mediante a confirmação da condição, estratégias de tratamento para manutenção e controle devem ser executadas (1,88). Diante dessa importância, gravidade e repercussão, os animais não podem ser sentenciados completamente mediante aferições mal-conduzidas.…”
Section: Diagnósticounclassified
“…Several factors affect results of blood pressure (BP) measurements in conscious dogs in a clinical environment. Relevant examples include breed, [1][2][3][4] sex, [5][6][7] age, [8][9][10][11] operator and operator experience, 12,13 and owner presence during measurements. 2 Types of measurement device, 14,15 and cuff size and placement, 16,17 are other factors that might affect BP measurement results.…”
Section: Introductionmentioning
confidence: 99%